The History of Forensic Linguistics as an Assisting Tool in the Analysis of Legal Terms - Houtman Houtman; Suryati Suryati (Faculty of Law, Sriwijaya University, Indonesia, 2018)
One dimension of human life which become the issue and had been debated is about the used of legal terms which is against the language rules. The use of language and law are often oriented to non-substance issues, namely the used of formal legal terms which is inconsistent with the standard of the Indonesian language. As a result, such a linguistic study does not provide a functional and proportional impact in resolving the problems of the law itself. The study only becomes as an analysis report on the forms of error in the use of language in the realm of law which is expected to be a feedback for improving the quality of the language of law enforcement officers. Accordingly, the empowerment of forensic linguistics as a tool to solve the legal problems becomes important and made a choice in the field of science, especially in the universities. The various cases developing both in domestic and foreign countries have absolutely proven beneficial for forensic linguistic analysis. A lawsuit that comes from speech and transcribed in written language can be a preliminary proof the reporters used. This is also become complaint to the Police. The article examines whether forensic linguistics can be inferred unlawful speech.